Future temporal focus in resilience research: when leader resilience provides a role model. Issue 7 (20th July 2020) - Lin, Tzu-Ting; Liao, Yuanhsi
Abstract : Purpose: Despite more and more researchers recommend that time-related issues should be considered into the resilience research, temporal issue is still largely neglected in empirical domain. The purpose of this study is to introduce the concept of future temporal focus, while investigating whether and when leader resilience contributes to subordinates' level of conveyed resilience. Design/methodology/approach: Survey responses from a two-source field study involving 222 supervisor–subordinate dyads were collected. Regression-based moderation and bootstrapping analyses were adapted to analyze data and test hypotheses by using the PROCESS syntax in SPSS software. Findings: Results showed that there is no significant effect of leader resilience on subordinate resilience. However, consistent with hypotheses, leader's future temporal focus and resilience had a significant interactive effect on subordinate's resilience. That is, when leaders had higher level of future temporal focus, their resilience would be positively correlated with subordinate resilience. Practical implications: The findings of the study provide important practical insights into developing relevant training and intervention programs in organizations to cultivate employee resilience. These can also be strengthened by encouraging leaders' future-oriented cognition on work-related domains and leader–member exchange relationship. Originality/value: Overall, this study introduced temporal focus into resilience theory by providing evidence of its impacts on employee behaviors, and emphasized the important role of future temporal focus of leader.